Distribution and functional traits of small mammals across the Mediterranean area: landscape composition and structure definitively matter. (February 2022) - Paniccia, Chiara; Laura Carranza, Maria; Frate, Ludovico; Di Febbraro, Mirko; Rocchini, Duccio; Loy, Anna
Highlights: Small mammals' taxonomic and functional composition vary with landscape pattern. Species assemblages tend to be simpler in anthropogenic landscapes. Seminatural and anthropogenic landscapes influence functional composition. Understanding community assembly could help prioritise conservation actions. Abstract: Mediterranean landscapes constitute a biodiversity hotspot where species distribution and composition have been shaped by a long history of traditional land use. In this work, we investigated the effects of landscape patterns on community composition and the functional, morphological, and ecological traits of 21 small mammal species in the Mediterranean region. We extracted species abundance and trait data from 86 georeferenced Common Barn-owl pellet sites collected in Central Italy, covering 33, 000 km 2, and stored in the OpenMICE database. Additionally, we measured 12 landscape metrics on land cover maps produced at intervals coeval with pellet collection dates. We explored the variation in species composition against landscape pattern metrics using canonical correspondence analysis (CCA). Moreover, we analysed the relationships among small mammals' occurrence, their life history traits, and landscape pattern metrics using the fourth-corner model approach. Our results highlighted the key role of landscape composition and configuration in shaping small mammal species composition and their functional traits. Species and trait composition varied along two main landscape gradients, with a simplification of species assemblage towards increasing human pressure (i.e., artificial surfaces and agricultural areas) and decreasing cover of seminatural areas. The observed variability of species assemblages and functional traits across Mediterranean landscape gradients highlights the need to preserve diverse ecosystems and land cover types to maintain small mammal biodiversity and related ecosystem functioning.